EVALUASI KEBIJAKAN PENGELOLAAN DANA DESA DI DESA PATTONDONSALU KECAMATAN MAIWA KABUPATEN ENREKANG TAHUN 2018 - Karmila Karmila; Muhammad Arisal Asad; Rahman Yakub (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine the evaluation of village fund management policies in Pattondonsalu Village, Maiwa District, Enrekang Regency in 2018. The population of this study is a large population with a population of 200 people. Samples were taken as many as 60 people. Data was obtained by distributing questionnaires or questionnaires. The data obtained from the questionnaire was then processed by descriptive statistical analysis with the SPSS.20 computer program. The results of this study are based on evaluation criteria and are categorized based on the categorization of Putra Eko Widjoko, evaluation of village fund management policies in Pattondon Salu Village, Maiwa District, Enrekang Regency in 2018 for the effectiveness criteria are in the very good category, the efficiency criteria are in the good category, the adequacy criteria are in the very good category. Good, the alignment criteria are in the very good category, the responsiveness criteria are in the very good category, and the accuracy criteria are in the very good category.With this research, it is hoped that it can be taken into consideration or reference for similar research, and it is also hoped that it can be developed further to expand and add new knowledge so that the results of further research will be better.